Awareness of Chronic Kidney Disease, Medication, and Laboratory Investigation among Tertiary Care Hospitals in Karachi - Syed Tajammul Ali, Amani Amir, Farzana Adnan, Farya Moon, Sadiqa Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Chronic kidney disease (CKD) continues to remain high globally, up to 13.4% by one estimate. Objectives: The main objective of the study is to find the awareness of chronic kidney disease, medication, and laboratory investigation in different tertiary care hospitals in Karachi, Pakistan. Material and methods: This cross-sectional study was conducted in Naimat Baigum hospital and different tertiary care hospitals in Karachi, Pakistan. The data was collected with the permission of ethical committee of hospital. Informed consent was taken from all the selected patients. The data was collected through a designed questionnaire which include all the basic and demographic data. Results: The data was collected from 1000 patients of both genders. The mean age range was 45±5.67 years. The median age, blood pressure, blood urea nitrogen, serum creatinine and urine specific gravity were presented in table 01. Patients with CKD had significantly lower hemoglobin, and higher reticulocyte counts, CRP and inflammation also present in patients with CKD. Conclusion: It is concluded that awareness about CKD in patients were low and its prevalence continues to remain high and is likely to increase globally. Keywords: CKD, Patients, Nephrology, CRP, BUN